2009
DOI: 10.1039/b909877a
|View full text |Cite
|
Sign up to set email alerts
|

The thermodynamics of lipid ion channel formation in the absence and presence of anesthetics. BLM experiments and simulations

Abstract: It is known that lipid membranes become permeable in their melting regime. In microscopic conductance measurements on black lipid membranes one finds that conduction takes place via quantized events closely resembling those reported for protein ion channels. Here, we present data of ion currents through black lipid membranes in the presence and absence of the anesthetics octanol and ethanol, and compare them to a statistical thermodynamics model using parameters that are obtained from experimental calorimetric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 58 publications
6
46
0
Order By: Relevance
“…There are no reports on neuronal growth in temperature microgradients in the literature, but it is known that bulk neuronal development is temperature-dependent (Ishida and Cheng, 1991;Fukui et al, 1992), and that some organisms (nematodes) have been shown to be extremely temperature sensitive, exhibiting thermotaxis up temperature gradients as small as 10 −4 • C/cm (Pline et al, 1988). It also seems that depolarization of the neuronal membrane is highly dependent on small variations in thermodynamic variables like temperature (Wunderlich et al, 2009;Blicher et al, 2009;Andersen et al, 2009;Wodzinska et al, 2009).…”
Section: Potential Trp Channel Activation In Optical Neuronal Guidancementioning
confidence: 99%
See 1 more Smart Citation
“…There are no reports on neuronal growth in temperature microgradients in the literature, but it is known that bulk neuronal development is temperature-dependent (Ishida and Cheng, 1991;Fukui et al, 1992), and that some organisms (nematodes) have been shown to be extremely temperature sensitive, exhibiting thermotaxis up temperature gradients as small as 10 −4 • C/cm (Pline et al, 1988). It also seems that depolarization of the neuronal membrane is highly dependent on small variations in thermodynamic variables like temperature (Wunderlich et al, 2009;Blicher et al, 2009;Andersen et al, 2009;Wodzinska et al, 2009).…”
Section: Potential Trp Channel Activation In Optical Neuronal Guidancementioning
confidence: 99%
“…It has been shown that chemical guidance of growth cones is mediated by an asymmetric influx of calcium ions Ca 2+ ) and the neuronal transient receptor potential (TRP) channels appear to be the key sensors and mediators in the process (Wang and Poo, 2005;Talavera et al, 2008;Li et al, 2005;Sappington et al, 2009). It is know that TRP channels can be activated by depolarization of the cell using chemical guidance factors or by an increase in temperature (Talavera et al, 2008;Caterina et al, 1997) and highly localized heating (Huang et al, 2010), and there is strong evidence in general that depolarization of the neuronal membrane is highly sensitive to small variations in thermodynamic variables like temperature and pressure (Wunderlich et al, 2009;Blicher et al, 2009;Andersen et al, 2009;Wodzinska et al, 2009). We therefore propose the hypothesis that the optical neuronal guidance is mediated by laser-induced heating, in particular by influx of Ca 2+ -ions due to heat-induced activation of neuronal TRP channels, discussed more thoroughly in Section 4.1.…”
Section: Introductionmentioning
confidence: 99%
“…But in our case the MSOGH model actually describes the much less abstract growth of a solid domain. Simulations presented in [9] show that even at a few degrees above T m , solid domains form in the membrane.…”
Section: Data and Analysismentioning
confidence: 99%
“…A typical result of the BLM experiment described in the text (see also Refs. [8] and [9]). This current trace was obtained at a 210 mV transmembrane voltage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation